The Role of Specialized Instruments for Advanced Endoscopic Resections in Gastrointestinal Disease - Markus Brand; Karl-Hermann Fuchs; Joel Troya; Alexander Hann; Alexander Meining (Life, 2023)
Introduction: Advanced endoscopic therapy techniques have been developed and have created alternative treatment options to surgical therapy for several gastrointestinal diseases. This work will focus on new endoscopic tools for special indications of advanced endoscopic resections (ER), especially endoscopic submucosal dissection (ESD), which were developed in our institution. This paper aims to analyze these specialized instruments and identify their status. Methods: Initially, the technical process of ESD was analyzed, and the following limitations of the different endoscopic steps and the necessary manipulations were determined: the problem of traction–countertraction, the grasping force needed to pull on tissue, the instrument tip maneuverability, the limited angulation/triangulation, and the mobility of the scope and instruments. Five instruments developed by our team were used: the Endo-dissector, additional working channel system, external independent next-to-the-scope grasper, 3D overtube working station, and over-the-scope grasper. The instruments were used and applied according to their special functions in dry lab, experimental in vivo, and clinical conditions by the members of our team. Results: The Endo-dissector has a two-fold function: (1) grasping submucosal tissue with enough precision and strength to pull it off the surrounding mucosa and muscle, avoiding damage during energy application and (2) effectively dividing tissue using monopolar energy. The AWC system quickly fulfills the lack of a second working channel as needed to complete the endoscopic task on demand. The EINTS grasper can deliver a serious grasping force, which may be necessary for a traction–countertraction situation during endoscopic resection for lifting a larger specimen. The 3D overtube multifunctional platform provides surgical-like work with bimanual-operated instruments at the tip of the scope, which allows for a coordinated approach during lesion treatment. The OTSG is a grasping tool with very special features for cleaning cavities with debris. Conclusions: The research and development of instruments with special features can solve unmet needs in advanced endoscopic procedures. The latter may help to increase indications for the endoscopic resections of gut lesions in the future.